Application of immune checkpoint targets in the anti-tumor novel drugs and traditional Chinese medicine development - Yuli Wang; Xingyan Zhang; Yuyan Wang; Wenjing Zhao; Huling Li; Lixing Zhang; Xinping Li; Tiejun Zhang; Hongbing Zhang; He Huang; Changxiao Liu (Elsevier, 2021)
Immune checkpoints are the crucial regulators of immune system and play essential roles in maintaining self-tolerance, preventing autoimmune responses, and minimizing tissue damage by regulating the duration and intensity of the immune response. Furthermore, immune checkpoints are usually overexpressed in cancer cells or noninvasive cells in tumor tissues and are capable of suppressing the antitumor response. Based on substantial physiological analyses as well as preclinical and clinical studies, checkpoint molecules have been evaluated as potential therapeutic targets for the treatment of multiple types of cancers. In the last few years, extensive evidence has supported the immunoregulatory effects of traditional Chinese medicines (TCMs). The main advantage of TCMs and natural medicine is that they usually contain multiple active components, which can act on multiple targets at the same time, resulting in additive or synergistic effects. The strong immune regulation function of traditional Chinese medicine on immune checkpoints has also been of great interest. For example, Astragalus membranaceus polysaccharides can induce anti-PD-1 antibody responses in animals, and these antibodies can overcome the exhaustion of immune cells under tumor immune evasion. Furthermore, many other TCM molecules could also be novel and effective drug candidates for the treatment of cancers. Therefore, it is essential to assess the application of immune checkpoints in the development of new drugs and TCMs. In this review, we focus on research progress in the field of immune checkpoints based on three topics: (1) immune checkpoint targets and pathways, (2) development of novel immune checkpoint-based drugs, and (3) application of immune checkpoints in the development of TCMs.